2012
DOI: 10.1111/j.1467-8667.2012.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet‐Based Detection of Beam Cracks Using Modal Shape and Frequency Measurements

Abstract: When a structure is subjected to dynamic or static loads, cracks may develop and the modal shapes and frequencies of the cracked structure may change accordingly. Based on this, a new method is proposed to locate beam cracks and to estimate their depths. The fault‐induced modal shape and frequency changes of cracked structures are taken into account to construct a new hybrid crack detection method. The method includes two steps: crack localization and depth estimation. The locations of the cracks are determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 61 publications
1
65
0
Order By: Relevance
“…Reduced stiffness resulting from damage to members and loosening of connections can be detected through changes in the structural dynamic response. The safety of the structure can be assessed using acceleration data (Adewuyi and Wu 2011;Figueiredo et al 2011;Talebinejad et al 2011;Osornio-Rios et al 2012;Qiao et al 2012;Xiang and Liang 2012;Jiang et al 2012). Accurate assessment of safety, however, is difficult, due to the analytical limitation and the fact that numerous assumptions must be made in the assessment process, considering the inherent uncertainties of large and complex civil structures.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced stiffness resulting from damage to members and loosening of connections can be detected through changes in the structural dynamic response. The safety of the structure can be assessed using acceleration data (Adewuyi and Wu 2011;Figueiredo et al 2011;Talebinejad et al 2011;Osornio-Rios et al 2012;Qiao et al 2012;Xiang and Liang 2012;Jiang et al 2012). Accurate assessment of safety, however, is difficult, due to the analytical limitation and the fact that numerous assumptions must be made in the assessment process, considering the inherent uncertainties of large and complex civil structures.…”
Section: Introductionmentioning
confidence: 99%
“…Though, the mode shape and its derivatives are most appropriate to localize the damage, because they are less effective for the damage quantification. Xiang et al [17] proposed a hybrid method using mode shape and natural frequency measurements. First, the damage is localized using the mode shape.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations to identify damage in these kinds of structures have been proposed; unfortunately, most of them deal with identifying just one damage or isolated damage. In real life, truss-type structures can be affected by several damage such as loosening of bolted connections (Mehrjoo et al, 2008;Yan et al, 2012), cracks Xiang and Liang, 2012), missing elements (Taha, 2010), reduced stiffness (RS) (Law et al, 2005;Lei et al, 2012), and corrosion (Batis and Rakanta, 2005;. Moreover, in a real structure, two or more types of damage can be present at the same time, and it has been shown that one kind of damaged condition can interfere with the detection of another kind of damage, leading to an incorrect assessment about the structure condition (Yan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most popular methods for structure condition monitoring are: Hilbert-Huang transform (HHT) (Mao and Que, 2006;Rezaei and Taheri, 2011;Razi et al, 2011), wavelet analysis (Han et al, 2005;Guo et al, 2005;Ren and Sun, 2008;Xiang and Liang, 2012), and multiple signal classification analysis (MUSIC) . For example, Guo et al (2005) investigated the use of wavelet packet transform (WPT) to extract features of vibration test data from a structure, where the wavelet energy rate index was the feature extracted and combined with an artificial neural network (ANN) to detect crack damage in a multi-story structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation